NORMAL MICROFLORA OF THE GASTROINTESTINAL TRACT (International journal of medical sciences, 2025)
The normal microflora of the gastrointestinal tract (GI) is one of the most important physiological systems of the human body, and its composition and functional state determine many aspects of the health of the macroorganism. As a result of metagenomic studies (16S rRNA profiling, whole genome sequencing and metabolomics) in the last decade, the phylogenetic and functional diversity of the GI microbiota has been radically reassessed. It is currently established that 90-99% of the intestinal microbiota in healthy adults is composed of the phyla Firmicutes, Bacteroidetes, Actinobacteria and Verrucomicrobia, of which the most important functional representatives are Faecalibacterium prausnitzii, Akkermansia muciniphila, Roseburia intestinalis, Eubacterium rectale, Bifidobacterium longum and Bacteroides thetaiotaomicron species. This complex of microorganisms not only ensures the absorption and metabolism of nutrients, but also forms the mucosal immune system, creates a barrier against the colonization of pathogenic microorganisms, synthesizes short-chain fatty acids (acetate, propionate, butyrate), vitamins (K, group B), neurotransmitters (GABA, serotonin) and other bioactive compounds, and directly affects the activity of the central nervous system through the "gastrointestinal-brain" axis.